A New Electrochemical Sensor Based on Carbon Black Modified With Palladium Nanoparticles for Direct Determination of 17α‐Ethinylestradiol in Real Samples. Issue 5 (5th January 2022) - dos Santos Fernandes, Juliana; Fernandes, Julia Oliveira; Bernardino, Cassiano Augusto Rolim; Mahler, Claudio Fernando; Braz, Bernardo Ferreira; Santelli, Ricardo Erthal; Cincotto, Fernando Henrique
Abstract: Electrochemical sensors to quantify concentrations of emerging pollutants have attracted great attention from the industry and scientific community. Nanomaterials such as carbon black have been applied in sensors to identify substances that are toxic to the environment and human health due to their excellent electroanalytical properties. The aim of the study was to develop a novel electrochemical sensor for the endocrine disruptor hormone determination. To our knowledge, for the first time the synthesis of material based on carbon black containing immobilized palladium nanoparticles, with the application for the hormone ethinylestradiol, is reported in the literature. The material was synthesized, characterized, and applied to the determination in tap water and human urine of the synthetic hormone 17α‐ethinylestradiol (EE2), which is currently considered an emerging pollutant. The morphology, structure and electrochemical performance of the sensors were characterized by scanning electron microscopy (SEM) and cyclic voltammetry (CV). Differential pulse voltammetry (DPV) in sodium phosphate buffer solution at pH 5.0 allowed the generation of a method to quantify the concentration of 17α‐ethinylestradiol in a linear range of 0.5–119.0 μmol L −1, obtaining 81.0 nmol L −1 of calculated limit of detection (LOD). The system was efficient in detecting 17α‐ethinylestradiol in real urine samples and showed no interferences for ascorbic acid, uric acid, progesterone, and dopamine. It is noteworthy that the results obtained showed good recovery values, considering that the urine samples were not previously treated or pre‐concentrated, which suggests the development of an electrochemical sensor that works in situ and in real time to monitor relevant substances in the control clinical and environmental, with the possibility of point‐of‐care analyses. Abstract :